Unknown interiors of ancient Egypt: producing by artificial intelligence in the context of light-space relationship - Çelik, Tuğçe (Journal of Architecture and Urbanism, 2025)
This study presents a design method aimed at visualizing cultural heritage through the architecture of ancient Egypt using modern technologies. With the deepening of the digital age, the use of digital technology and artificial intelligence in cultural heritage research has become an important tool for renewing and disseminating period architecture. The reason for choosing the interior spaces of ancient Egypt as a sample in this study is that, in addition to leaving a rich heritage in the field of architecture, ancient Egypt offers distinct period architecture in terms of space-light relationship. As a result of literature review, keywords related to architecture and the relationship between space and light in the Ancient Period were identified, and the study was visualized using the state-of-the-art artificial intelligence technology of today, namely human-computer interaction combined with text-to-image technology. The motivation and aim of this study is to demonstrate the role of reanimating cultural heritage like ancient period architectures in the computer environment based on interpretation, contributing to architectural sustainability, and spreading to future periods.